Pengaruh Profitabilitas, Struktur Modal, Ukuran Perusahaan, Dan Good Corporate Governance terhadap Nilai Perusahaan - Widya Kusuma Wardhani; Kartika Hendra Titisari; Suhendro Suhendro (Universitas Batanghari Jambi, 2021)
This research aims to know and analyze the impact of profitability, capital structure, company size and good corporate governance on firm value. The dependent variable in this research is firm value. While the independent variables used in this research are profitability, capital structure, company size, board of commissioners and audit committee. The population of this research is the entire consumer goods industry sector company listed on the Indonesia Stock Exchange period in 2015-2019. The sample selection in this research using purposive sampling method with certain criteria thus obtained a sample of 20 consumer goods industry companies listed on the IDX period in 2015-2019. The data used is secondary data sourced from annual report. The data analysis technique used double linear regression analysis. The results showed that profitability and company size affect the value of the company. Meanwhile, capital structure, board of commissioners and audit committee do not affect the company’s value in consumer goods industry company period from 2015-2019.